Explaining the Oscillation of Cross-Strait Relations: A Domestic Approach. (March 2020) - Wang, T.Y.
This special section includes four papers to examine the ups and downs of the relationship between Taiwan and China. While both sides of the Taiwan Strait have different political systems, these studies show that domestic politics play a central role in explaining the oscillation of the cross-Strait relationship. The findings provide evidence of the interaction between domestic and external factors. Leaders in Beijing and Taipei therefore need to take heed of the internal forces of both sides of the Taiwan Strait in addressing their contentious relationship.